FACTORS AFFECTING FIRM VALUE IN BANKING FIRM IN INDONESIA - Rosalia, Vicky (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of this research was to examine and analyze the Effect of Corporate Governance Measured by Institutional Ownership, Independence of the Board of Commissioners, Audit Committee, and Audit Quality on Company Values. This study also examined the effect of Profitability in moderating the relationship between Corporate Governance and Corporate Value. This research is causative research. The population in this research are banking companies listed on the Indonesia Stock Exchange in the period 2015-2017 with 43 companies. The sampling technique used was purposive sampling based on certain criteria. Based on these criteria, a sample of 41 companies with 3 years of observation was obtained so that the total sample number was 123. Based on data research by using multiple linear regression analysis and residual test for moderating variables. The results of the research show that Corporate Governance Measured by Institutional Ownership, Independence of the Board of Commissioners, Audit Committee, and Audit Quality have an effect on the Company's Value simultaneously. While partially Institutional Ownership, Audit Committee, and Audit Quality have a significant effect on Company Value, while the Independence of the Board of Commissioners does not significantly influence the Company's Value. For the moderating variable, Profitability is not able to moderate the relationship of Institutional Ownership, Independence of the Board of Commissioners, Audit Committee, and Audit Quality towards Corporate Values.